Statement of the problem of development in the context of the relationship "subject-environment". - Abdumalikova Nilufar Zakirovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Based on the relations of opposition between the subject and the environment, two scientific directions are distinguished: endogenous, where the subject is considered the main driving force, and exogenous, where the environment is considered the driving force. Exogenous means arising as a result of external factors, endogenous - arising, developing due to internal causes. Endogenous is usually understood as hereditarily determined. The terms exogenous - endogenous are used to characterize the sources of mental illness and the reasons for the individual originality of their course.